Strategic Human Resource Development in the Society 5.0 Era: a Systematic Literature Review of Scopus Q1/Q2 Studies - Filo Leonardo Tinggogoy; Ade Putra Ode Amane; Samkamaria Samkamaria; La Ode Sabirila Jayalangi (UIN Sunan Gunung Djati, 2025)
This study aims to analyze human resource (HR) development strategies in the Society 5.0 era through the Systematic Literature Review (SLR) approach. The Society 5.0 era, which is characterized by seamless integration between physical and cyberspace, has created a new paradigm in HR development, where technology is not only a tool but has become an integral part of life. Through an analysis of 20 Scopus indexed articles (Q1 and Q2) published in the 2019-2024 period, this study identified several key findings. The results show that digital transformation in HR development requires a holistic approach that includes aspects of technology, humans, and organizations. The implementation of technologies such as AI and VR/AR has been shown to increase learning effectiveness by up to 2.5 times, while a structured hybrid learning approach results in a 65% higher level of knowledge application than traditional methods. The study also revealed the importance of a learning culture and change management, where 72% of digital learning initiatives fail due to cultural resistance. The measurement framework developed includes dimensions of financial metrics, learning metrics, and organizational impact, providing comprehensive guidance for organizations in implementing HR development strategies in the Society 5.0 era. The implications of the research emphasize the importance of balance between technology adoption and human values, as well as the formation of a sustainable learning ecosystem.